To combat cow flu outbreak, scientists plan to infect cattle with influenza in high-security labs: Novel effort comes as study finds key receptor for avian flu virus in udders - Kupferschmidt, Kai (2024)
The avian influenza virus that has been infecting dairy cows and spreading alarm in the United States was expected to reach Germany this week. But that’s actually good news. A shipment of samples of the H5N1 virus from Cornell University virologist Diego Diel is destined for the Federal Research Institute for Animal Health in Riems, which has one of the rare high-security labs worldwide that are equipped to handle such dangerous pathogens in cattle and other large animals. There, veterinarian Martin Beer will use the samples to infect dairy cows, in search of a fuller picture of the threat the virus poses, to both cattle and people, than researchers have been able to glean from spotty data collected in the field.